Efficacy and safety of CT-guided 125I seed implantation by coplanar template as a salvage therapy for vertebral metastases after failure of external beam radiation therapy: a retrospective study - Li, Peishun; Bai, Yunling; Yuan, Qianqian; Man, Qirong; Xing, Chao; Ren, Yanchen; Zhang, Kaixian (Frontiers in Oncology, 2023)
Purpose: To evaluate the efficacy and safety of computed tomography (CT)-guided125I seed implantation by coplanar template for vertebral metastases after failure of external beam radiation therapy (EBRT). Material and methods: Retrospective analysis of the clinical outcomes of 58patients with vertebral metastases after failure of EBRT, who underwent 125I seed implantation as a salvage treatment with a CT-guided coplanar template-assisted technique from January 2015 to January 2017. Results: The mean post-operative NRS score decreased significantly at T4w (3.5 ± 0.9, p<0.01), T8w (2.1 ± 0.9, p<0.01), T12w (1.5 ± 0.7, p < 0.01) and T6m (1.2 ± 0.6, p < 0.01) respectively. The local control rates after 3, 6, 9 and 12 months were 100% (58/58), 93.1% (54/58), 87.9% (51/58), and 81% (47/58), respectively. The median overall survival time was 18.52months (95% CI, 16.24-20.8), and 1- and 2-year survival rates were 81% (47/58) and 34.5% (20/58), respectively. By performing a paired t-test analysis, there was no significant difference in D90, V90, D100, V100, V150, V200, GTV volume, CI, EI and HI between preoperative and postoperative(p＞0.05). Conclusions: 125I seed implantation can be used as a salvage treatment for patients with vertebral metastases after failure of EBRT.